Kinerja Penyaluran Kredit Usaha Mikro Kecil dan Menengah (UMKM) oleh Perbankan di Indonesia periode Tahun 2013 – 2018 - Aliudin, Raden Muhammad Tedy (www.bsi.ac.id, 2019)
Abstact - Micro, Small and Medium Enterprises that reach more than 99% of total business in Indonesia, in addition to being a stronghold of defense in various state crises, also contribute greatly to Indonesia's economic growth, but have not received optimal support in terms of financing / credit from banks. . Bank Indonesia has stipulated a regulation that requires banks to channel loans to micro, small and medium enterprises as low as 20% of total lending, no later than 2018 must be fulfilled. So to find out the achievement of bank credit / financing distribution to Micro, Small and Medium Enterprises, a data study is needed to show overall banking performance.Keyword: Micro, Small, and Medium Enterprises